Genome identification and diversity analysis of banana (Musa spp.) from Jember based on morphological characters - Sari, Vega Kartika; Sa'diyah, Halimatus; Rusdiana, Riza Yuli; Hartatik, Sri; Hariyono, Kacung (AGROMIX, 2024)
Introduction: Banana plants are easy to find and grow in Indonesia, including in Jember. Banana production in Jember in 2020 increased by 50% and has the potential to be inventoried and developed. Information regarding the characteristics of various banana cultivars is needed for future banana breeding. This research was conducted to identify and classify the genome of bananas growing in Jember and determine the level of banana diversity. Methods: The banana exploration using a purposive sampling method. The observation of 15 morphological characters followed the method of Simmonds and Shepherd. Determination of the genome followed the method of Silayoi & Chamchalow and Singh & Uma. The kinship analysis uses cluster analysis using the average linkage method and Gower distance, by R Studio software. Results: There were 23 banana cultivars obtained in this research, consisting of 35% dessert bananas and 65% plantain types. Genome identification results in four genome groups, namely AA/AAA, AAB, ABB, and BB. Cluster analysis produces three main groups, where its branch is generally consistent with the genome grouping. The closest relationship is between Rayap and Seribu bananas (0.96), while the furthest is between Gaje and Agung bananas (0.38). The dissimilarity value for 23 banana cultivars is 0.36, or the similarity is 0.64. Conclusion: The 23 banana cultivars are closely related or have low diversity based on the 15 morphological characters observed. Further identification can be carried out with a greater number of morphological characters, accompanied by molecular identification.